Defect-free drying of large fine-particle zirconia compacts prepared by gelcasting method. Issue 15 (December 2022) - Trunec, Martin; Stastny, Premysl; Kastyl, Jaroslav
Abstract: In this work, drying of bodies prepared by gelcasting fine submicrometre-sized zirconia particles was studied and a drying process for defect-free bodies with large cross-sections was proposed. It was found that the cracking of large bodies could be prevented by reducing the monomer content and using appropriate non-volatile cosolvents. Glycerol and polyethylene glycols with different molecular weights were used as non-volatile cosolvents in aqueous ceramic suspensions. The complex effects of the individual cosolvents on the gelcasting process and, in particular, on the drying step were investigated and explained. The applicability of individual cosolvents for the gelcasting process were discussed and their optimal use was indicated.